Suicide risks associated with pregnancy outcomes: a national cross-sectional survey of American females 41–45 years of age - David C. Reardon (Journal of Psychosomatic Obstetrics and Gynecology)
Objective Numerous studies have linked abortion to an elevated risk of suicide. One hypothesis is that this association is entirely incidental and most likely fully explained by preexisting mental illness. This hypothesis can be tested by examining women’s own self-assessments of the degree, if any, that abortion and other pregnancy outcomes contributed to suicidal thoughts and behaviors.Methods A topic blind survey was distributed to 2829 American females 41–45 years of age. Respondents were asked about any history of attempted suicide(s) and reproductive histories. Grouped by reproductive history, respondents were then asked to rank on visual analog scales the degree, if any, to which their pregnancy outcome contributed to suicidal thoughts, self-destructive behaviors, and any attempted suicides.Results Aborting women were twice as likely to have attempted suicide compared to other women. Aborting women, especially those who underwent coerced or unwanted abortions, were significantly more likely to say their pregnancy outcomes directly contributed to suicidal thoughts and behaviors compared to women in all other groups.Conclusions The hypothesis that higher rates of suicide following abortion can be entirely explained by preexisting mental health problems is inconsistent with women’s own self-assessments of the degree their abortions directly contributed to suicidal and self-destructive behaviors.